Roles query algorithm in cloud computing environment based on user require - YANG Liu; TANG Zhuo; LI Ren-fa; ZHANG Zong-li (Tongxin xuebao)
Roles based access control model CARBAC for cloud computing environment was proposed.Roles in the model include user roles and resources owner roles,the latter were called administrator roles.For the resources owner roles assigning the roles to the users,roles query algorithm in the hybrid hierarchies based on users’ access require was proposed.Through this algorithm,for the certain privileges set,this model could choose the least roles set to be assigned to the users.The simulation experiment indicates that for the mass user access,this algorithm can reduce the roles quan-tity,shorten the authorization procedure,and advance the system efficiency.